A hospital-wide initiative to eliminate or reduce needle pain in children using lean methodology. (September 2018) - Friedrichsdorf, Stefan J.; Eull, Donna; Weidner, Christian; Postier, Andrea
Abstract: Introduction: Pain remains common, underrecognized, and undertreated in children's hospitals and pediatric clinics. Over 200, 000 patients experience needle pain annually in our institution, caused by blood draws, intravenous access, vaccinations, and injections on all inpatient units, emergency departments, outpatient laboratories, and ambulatory clinics. Objectives: We implemented a hospital-based, system-wide initiative called the "Children's Comfort Promise, " and created a new standard of care for needle procedures that required staff to consistently offer 4 strategies: (1) topical anesthetics, (2) sucrose or breastfeeding for infants 0 to 12 months, (3) comfort positioning (including swaddling, skin-to-skin, or facilitated tucking for infants; sitting upright for children), and (4) age-appropriate distraction. Methods: The protocol was established system-wide in one of the largest children's hospitals in the United States using a staggered implementation approach over a 3-year period to allow for unit-specific customization and facilitation of knowledge transfer from one unit to another. All departments were required to offer all 4 strategies with appropriate education at least 95% of the time. Results: Comparison of baseline audits with continuous postimplementation audits revealed that wait times for services decreased, patient satisfaction increased, and staff concerns about implementation were allayed (eg, concerns about wait times and success rates of venipuncture after topical anesthesia). Conclusion: This is the first report of a successful system-wide protocol implementation to reduce or eliminate needle pain, including pain from vaccinations, in a children's hospital across all inpatient units, emergency departments, outpatient laboratories, and ambulatory clinics through consistent use of topical anesthesia, sucrose/breastfeeding, positioning, and distraction. Abstract : Supplemental Digital Content is Available in the Text.